Spontaneous intraparenchymal otogenic pneumocephalus presenting with abrupt onset of coma. Issue 1 (February 2016) - Scuotto, A.; Cappabianca, S.; Capasso, R.; Natale, M.; D'Oria, S.; Rotondo, M.
Abstract: We report a case of spontaneous otogenic pneumocephalus, manifesting with a rapid deterioration of consciousness level. A 37-year-old man presented a 3-days history of headache and fluctuant confusion. On admission the patient was neurologically intact except for temporo-spatial disorientation. Brain Computed Tomography (CT) scan showed a large air collection in the left temporal lobe, causing mass effect. Hyperpneumatisation of mastoid air cells was also noticed. Because of the abrupt onset of coma (Glasgow Coma Scale = 10), emergency surgical evacuation of tensive pneumocephalus was carried out. Postoperatively, the patient quickly regained a good level of consciousness and was headache-free. Highlights: Spontaneous otogenic pneumocephalus generally presents with subtle symptoms. Sudden consciousness involvement is a rare onset condition. Hyperpneumatisation of the petrous bone is a predisposing factor.